Hypertrophic Nonunion Humerus Mimicking an Enchondroma - N. K. Magu; Amanpreet Singh; Reetadyuti Mukhopadhyay; Jitendra Wadhwani; Paritosh Gogna; Rohit Singla; Sahil Arora; Pragnashree Mukhopadhyay Chatterjee (Case Reports in Orthopedics)
Introduction. Although fractures of humeral shaft show excellent results with conservative management, nonunion does occur. Case Report. We bring forth the case of a young male with a 1.5-year-old hypertrophic nonunion of the humerus mimicking an enchondroma. The initial X-ray images of the patient appeared to be an enchondroma, which only on further evaluation and histopathological analysis was diagnosed conclusively to be a hypertrophic nonunion. Discussion. Enchondromas are often incidentally diagnosed benign tumours. It is however not common to misdiagnose a hypertrophic nonunion to be an enchondroma. We present this case to highlight the unique diagnostic dilemma the treating team had to face.